Perceptions of Resources for Safe Sex Behaviors and HIV Prevention among Male Adolescents - Pongtriang, Praditporn; Pothiboot, Sumontha; Soontorn, Thassanee (Princess of Naradhiwas University Journal, 2022)
This descriptive qualitative research aims to study perceptions of resources for safe sexbehaviors and HIV prevention among male adolescents. The informants in this study were 19 male adolescents over 18 years of age studying undergraduate degree in Surat Thani province. Data collection was conducted between December 2016 and March 2018 using a one-time semi-structured in-depth interview and focus group. The interview protocol was reviewed for research validity by two qualitative research experts. Content analysis was conducted following Creswell and Poth’s guidelines, and data were organized using the NVivo 11 software program. The research result revealed that resources supported perceptions of safe sex behaviors and HIV prevention consisted of two parts. The first part was the resources included academic resources and social resources. The second was the barrier to access appropriate resources which contained 3 aspects as follows: 1) the precariousness of media and imitative behavior, 2) the lack of privacy in health service center, and 3) the lack of resources and specific health services. The findings could be used as a guideline in terms of resource management for educational institutions and health service center in preventing HIV and sexual risk behaviors.